PERBANDINGAN EFEKTIVITAS PROPRIOCEPTIVE NEUROMUSCULARFACILITATION TERHADAP MUSCLE ENERGY TECHNIQUE PADA MECHANICAL NECK PAIN:A RANDOMIZED CONTROLLED TRIAL - Satria Nugraha, Made Hendra; Juni Antari, Ni Komang Ayu; Saraswati, Ni Luh Putu Gita Karunia (UI Scholars Hub, 2020)
Neck pain is a problem that often occurs in populations. One of them is mechanical neck pain (MNP). The clinical manifestation of MNP include: pain, range of motion limitation, muscle spasm and also accompanied by weaknesses in deep cervical muscles, and neck disabilities that interfere with the function of daily activities. The purpose of this study is to determine the differences in the effectiveness of the addition of proprioceptive neuromuscular facilitation (PNF) to muscle energy technique (MET) in a combination of ultrasound therapy (UST) and neck stabilization exercise (NSE). This research is a randomized controlled trial with pre and post-test control group design. The number of study participants in both groups is 24 respondents. In the control group (n = 12) were given UST, NSE, and PNF while in the treatment group (n = 12) were given UST, NSE, and MET. The outcome measure of this study include: movement pain is measured by visual analogue scale, lateral flexion cervical range of motion is measured by a goniometer, and neck disability is measured by the Indonesian version of the Northwick park neck pain questionnaire. Based on the results of the study, it can be concluded that: (1) The combination of UST + NSE + MET significantly reduces pain in MNP (p = 0,000), (2) the combination of UST + NSE + MET significantly increases the range of motion in MNP (p = 0,000), and (3) there is no significant difference between the control and treatment groups in reducing neck disability in MNP (p = 0.409).